2010
DOI: 10.1186/1471-2202-11-105
|View full text |Cite
|
Sign up to set email alerts
|

EphrinA5 protein distribution in the developing mouse brain

Abstract: Background EphrinA5 is one of the best-studied members of the Eph-ephrin family of guidance molecules, known to be involved in brain developmental processes. Using in situ hybridization, ephrinA5 mRNA expression has been detected in the retinotectal, the thalamocortical, and the olfactory systems; however, no study focused on the distribution of the protein. Considering that this membrane-anchored molecule may act far from the neuron soma expressing the transcript, it is of a crucial interest to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 66 publications
(119 reference statements)
2
7
0
Order By: Relevance
“…Next, we investigated the effects of ephrinA ligands for in vivo 5-HT axon targeting using an overexpression strategy. We focused on the amygdala and piriform cortex, which are preferential targets of the DR 5-HT neurons ( Muzerelle et al 2016 ) and express only very low levels of the main EphA5 ligands, ephrinA2, ephrinA3, and ephrinA5, based on our own observations, confirming previously published reports ( Deschamps et al, 2010 ; Gerstmann et al 2015 ) and available public resources (Allen Brain Atlas, http://developingmouse.brain-map.org/gene/show/ 1341 5 , 13416, 13418). This suggested that the amygdala and piriform cortex could be permissive for the ingrowth of DR axons that express high levels of EphA5 receptors.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Next, we investigated the effects of ephrinA ligands for in vivo 5-HT axon targeting using an overexpression strategy. We focused on the amygdala and piriform cortex, which are preferential targets of the DR 5-HT neurons ( Muzerelle et al 2016 ) and express only very low levels of the main EphA5 ligands, ephrinA2, ephrinA3, and ephrinA5, based on our own observations, confirming previously published reports ( Deschamps et al, 2010 ; Gerstmann et al 2015 ) and available public resources (Allen Brain Atlas, http://developingmouse.brain-map.org/gene/show/ 1341 5 , 13416, 13418). This suggested that the amygdala and piriform cortex could be permissive for the ingrowth of DR axons that express high levels of EphA5 receptors.…”
Section: Resultssupporting
confidence: 86%
“…EphA5 expression in 5-HT raphe neurons was dynamically expressed, being maximal during axon growth in embryonic life, reaching target during the early postnatal period, and showing decreased expression, similarly to what has reported for ephrinA5 expression ( Deschamps et al, 2010 ). Given the potential of 5-HT neurons to regenerate and grow, it will be interesting to know whether the present developmental mechanisms are reactivated after a lesion, and whether the propensity of serotonin axons to regrow ( Müllner et al, 2008 ) is linked to their EphA content.…”
Section: Discussionsupporting
confidence: 83%
“…82 Supplementation of PRDX6 has been shown to attenuate reactive oxygen species and TGFβ-induced insult to glaucomatous trabecular meshwork cells in vitro, as well as to decrease the senescence process in these cells. 83 Moreover, the glaucomatous neuroprotective effects of this antioxidant factor have been demonstrated on RGC, as demonstrated by observations that reactive oxygen species-mediated suppression of PRDX6 in these cells can be prevented by over-expression of PRDX.6 84 Observations that high levels of PRDX6 are expressed by Müller glia further support the antioxidant role of these cells within the retina. Production of this molecule by Müller glia upon retinal injury may limit the damage caused by reactive oxygen species on retinal neurons and may play a major neuroprotective role in many retinal degenerative diseases such as glaucoma and macular degeneration.…”
Section: Müller Glia As a Source Of Antioxidants In The Neural Retinamentioning
confidence: 94%
“…The expression of EphA7 by a subpopulation of striatal neurons during development makes this tyrosine kinase receptor a prime candidate for regulating intracompartmental sorting of matrix neurons. For example, several studies indicate that ephrins known to bind to EphA7 are expressed in the developing striatum (Passante et al, 2008;Cooper et al, 2009;Deschamps et al, 2009Deschamps et al, , 2010. Thus, EphA7 may interact with specific ephrins during development to facilitate the organization of striatal neurons into unique ''matrisome'' subcompartments within the matrix in a fashion similar to how other Eph receptors facilitate the formation of rhombomeres (Becker et al, 1994;Cooke et al, 2001Cooke et al, , 2005, mediate neural crest cell migration (Wang and Anderson, 1997;Krull et al, 1997;Koblar et al, 2000;McLennan and Krull, 2002;Kasemeier-Kulesa et al, 2006;Davy and Soriano, 2007;Kuriyama and Mayor, 2008), and establish cellular boundaries in the cortex (Vanderhaeghen et al, 2000;Miller et al, 2006).…”
Section: Epha7 Identifies a Unique Striatal Subcompartmentmentioning
confidence: 99%